Peran Keteladanan Guru dalam Internalisasi Nilai Al-Qur’an pada Sistem Pendidikan Boarding School Modern - Dewi T Dewi T; Rosmiati Ramli (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2026)
This study aims to analyze the role of teacher role models in the internalization of Quranic values ​​in a modern boarding school education system. The study employed a qualitative approach with a case study design, conducted at Muhammadiyah Boarding School MBS Rappang Junior High School. The subjects consisted of students, ustadz/ustadzah (teacher), and dormitory administrators, selected purposively. Data were collected through in-depth interviews, participant observation, and documentation, then analyzed using thematic analysis techniques with triangulation to ensure data validity. The results indicate that teacher role models play a significant role in the internalization of Quranic values, particularly through direct practice observed by students in their daily lives. The boarding school environment, which integrates academic activities and character development, strengthens the effectiveness of role models through continuous habituation. However, internalization of values ​​is not yet fully consistent, influenced by factors such as the influence of digital media, differences in student backgrounds, and limited personal interaction. In conclusion, teacher role models are a key strategy in developing Qur'anic-based character in students, which requires support from a conducive institutional environment that adapts to the challenges of the digital era. This research contributes to the development of role model-based learning models in modern Islamic education.